Strategi Pengembangan Sektor Unggulan di Kabupaten Mojokerto - Putri Citra Devi; Renggo Ais Aprilian; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to examine Mojokerto Regency's priority sector development plan. In this study, a qualitative, descriptive approach was used. Secondary data, collected by the researchers themselves from sources like websites, journals, bulletins (such as those found at the Statistics Agency), company or organizational documents, newspapers and magazines, and so on, are the basis for the analyses conducted in this study. Mojokerto Regency's agricultural industry is expanding at a quicker rate than most others right now. The tourist, agriculture, and industrial industries are the current focus of this leading sector development plan. Mojokerto Regency's rural setting, with all its potential assets like its natural resource assets, lends itself well to the growth of these two possible sectors or sub-sectors, which will ultimately boost the regional economy of Mojokerto Regency.